2011
DOI: 10.1186/1471-2407-11-476
|View full text |Cite
|
Sign up to set email alerts
|

GnRH receptor activation competes at a low level with growth signaling in stably transfected human breast cell lines

Abstract: BackgroundGonadotrophin releasing hormone (GnRH) analogs lower estrogen levels in pre-menopausal breast cancer patients. GnRH receptor (GnRH-R) activation also directly inhibits the growth of certain cells. The applicability of GnRH anti-proliferation to breast cancer was therefore analyzed.MethodsGnRH-R expression in 298 primary breast cancer samples was measured by quantitative immunofluorescence. Levels of functional GnRH-R in breast-derived cell lines were assessed using 125I-ligand binding and stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…In fact, the increased expression levels and IP response to GnRHa detected in GnRHR-transfected MDA cells, emulated those previously detected in breast cancer cells exhibiting high GnRHR expression levels [52]. Here we confirm that to detect relevant effects of GnRH on breast cancer cells function, it is necessary to substantially increase cell surface plasma membrane receptor levels, which is an important issue given that the number of GnRHRs is highly variable in malignant breast tumors tissue [51]. In this scenario, measurement of GnRHR density in malignant breast tissue may be useful as a surrogate marker to predict the tumor responsiveness to GnRHa administration.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In fact, the increased expression levels and IP response to GnRHa detected in GnRHR-transfected MDA cells, emulated those previously detected in breast cancer cells exhibiting high GnRHR expression levels [52]. Here we confirm that to detect relevant effects of GnRH on breast cancer cells function, it is necessary to substantially increase cell surface plasma membrane receptor levels, which is an important issue given that the number of GnRHRs is highly variable in malignant breast tumors tissue [51]. In this scenario, measurement of GnRHR density in malignant breast tissue may be useful as a surrogate marker to predict the tumor responsiveness to GnRHa administration.…”
Section: Discussionsupporting
confidence: 85%
“…To this end, we overexpressed the GnRHR in MDA cells and analyzed the effects of its cognate ligand on the pathways leading to actin cytoskeleton activation and cell adhesion. MDA cells transfected with the GnRHR (WT and DesK191) cDNAs, specifically bound 125 I]-Buserelin and produced higher levels of the second messenger IP in response to the GnRH analog than untransfected cells, overcoming the problem related to the low naturally expressed GnRHR levels in breast cancer cell lines [50,51]. In fact, the increased expression levels and IP response to GnRHa detected in GnRHR-transfected MDA cells, emulated those previously detected in breast cancer cells exhibiting high GnRHR expression levels [52].…”
Section: Discussionmentioning
confidence: 99%
“…However, lack of prohormone convertase and/or constitutive release was found to cause the release of these neuropeptides in a precursor form . In addition, there are many cases where these ectopic hormone‐producing tumors express their hormone‐specific receptors . However, precursor peptides usually show a low binding potential to their own specific receptors.…”
mentioning
confidence: 99%
“…A large number of studies have reported that BRCA is well known for being strongly in uenced by female steroids [28][29][30]. Inositol phosphate is also thought to play an essential role in BRCA [31]. In addition, we explored the relationships between drug-resistant and -sensitive dysregulated ceRNAs and cancer hallmarks.…”
Section: Cancer Hallmarks In Drug-resistant and -Sensitive-dysregulatmentioning
confidence: 99%